Perilaku Membela Konstruktif: Wujud Empati Bystander dalam Tindakan Pembelaan yang Prososial - Silvania, Olyn (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2024)
Bystander's responses can potentially strengthen or weaken the cyberbullying situation. However, the facts show that most bystanders choose to be passive rather than defend the victim. Nonetheless, passive bystander behavior does not necessarily mean approval of the perpetrator's actions. Some bystanders consider cyberbullying to be an unpleasant thing, so it can generate a sense of empathy for the victim. Unfortunately, a lack of self-efficacy and knowledge regarding how to deal with cyberbullying can inhibit bystanders from defending victims. Therefore, knowledge about constructive defending behaviors can help bystanders to defend victims in a good way. This article aims to provide knowledge about constructive defending behavior as an online prosocial behavior. This article explains that prosocial behavior theory is more relevant with constructive defending behavior than aggressive defending behavior. Then, constructive defending behavior can minimize cyberbullying because constructive defending behavior supports bystander emotion regulation, creates social norms related to positive online social interactions, and realizes social capital in the form of social ties. These social ties offer four useful resources, like information on how to deal with cyberbullying, social connectedness of bystanders with other social media users, potential bystander to be influent person who motivates other social media users to take constructive defense actions, and become a reinforcement of identity and a sense of worth to the victim. Hopefully, this article can provide an understanding that constructive defending behavior should be priority to develop by social media users.